STRATIFIED THREE-LAYER LUBRICANT FLOW IN THE GAP OF ELASTICALLY DEFORMABLE THRUST BEARING WITH INCREASED CARRYING CAPACITY - Kamill Samedovich Akhverdiyev; Victor Markovich Prikhodko; Sergey Vladimirovich Mitrofanov; Boris Evgenyevich Kopotun (Advanced Engineering Research)
On the basis of Navier — Stokes linear equations for the case of Lame “ thin layer ”, a technique of generating an exact self - similar solution to the hydrodynamic calculation of the elastically deformable thrust bearing with the pr ofile adapted to its bearing surface operating on a three - layer lubricant is presented. The effect of the par ameters characterizing the adapted contour supporting the slider surface, the su p porting layer deformation, viscous layer ratio, and their length, on the basic performance of the thrust bearing is evaluated. These paramete r values provi ding a rational oper ation according to the carrying capacity and friction force of the relevant thrust bearing are d efined. Furthermore, the optimal variation ranges of the constructive, operating, and all the functio nal parameters dete r mining the bearing performance, are set . The obtained results allow creating the database for designing thrust bearings operating on the three - layer lubrication.